(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Mating and oviposition behaviour of brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis Guenee (Lepidoptera:Pyralidae) were carried out in the laboratory on brinjal plants maintaining the temperature (20-250C) and relative humidity (80-85%). The moths were found active at night for mating and oviposition. Mating usually occurred at late night but a few moths were found to continue mating up to 8.0 hour of the day. Maximum moths completed mating between 4.00 to 6.00 hour of the day. Mating period ranged from 28-50 minutes. Mating occurred in first and second night of the adult emergence. Majority of the moths (90.80%) were found to mate in the first night and the rest went for mating in the following night. Oviposition always occurred at night. Females were always found to oviposit at night with an average 86.62% oviposition during the first half of the night. Again 60% egg deposition of first half of the night occurred during 20.00 to 22.00 hours. A female laid 241.50 eggs in an average of 2.70 days of oviposition. The egg laying pattern indicates that the egg laying continued for a maximum of 4 days showing a decreasing pattern of deposition with the increase of age. About 50% of the total eggs were deposited on the first day. The BSFB females preferred brinjal leaves for oviposition. Distribution of the eggs on the upper and lower surfaces of the leaves was found 1:2.74. Females showed higher preference for upper canopy of the brinjal plant as oviposition site. Bangladesh J. Agril. Res. 46(3): 285-296, September 2021